Pengaruh Kompres Air Hangat dan Air Dingin terhadap Nyeri Tulang Belakang Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Rajapolah - Aulia Yuspina; Nunung Mulyani; Uly Artha Silalahi (stikes dharma husada bandung, 2018)
Management of back pain during pregnancy varied such as pharmacological and nonpharmacological management, Physiological effects of warm compresses can relieve pain by relaxing the muscles, have sedative effects and relieve pain and cold compresses can make the area numb, slow the speed of nerve conduction thereby slowing the flow of pain impulses . The purpose of this study was to compare the level of back pain of trimester 3 pregnant women after warm and cold water compress. The research method used is quasi experiment type non-equivalent control group design. Sample in this research is pregnant mother of trimester 3 which examined its contents in work area of ​​Rajapolah health center and complain of back pain with accidental sampling technique total sample equal to 56 people The results showed that the value of back pain intensity on the warm compress treatment amounted to 1.61 while the intensity of back pain on the cold compress treatment was 0.57. So it can be concluded that cold compress is better than warm compress because the average value of the back pain is 0.57. The conclusion is that there are differences in pain levels before and after the warm and cold water compress, and cold compress better in the reduction of pain compared with warm compress. Suggestions for to be applied and taught to pregnant women with so it can help mothers to resolve their back pain.